A highly efficient, thermo stable and broad pH adaptable copper-zinc super oxide dismutase (AmSOD1) mediates hydrogen peroxide tolerance in Avicennia marina. (July 2021) - Fesharaki-Esfahani, Monireh; Shahpiri, Azar; Kazemi-Nasab, Akram
Abstract: Avicennia marina is a widely distributed mangrove species with high tolerance to salt, oxidative stress and heavy metals. In the preset work, we found that superoxide dismutase (SOD) activity increases in Avicennia marina leaves in response to salt and hydrogen peroxide. Monitoring the SOD using Western blot analysis revealed that the accumulation of SOD increased in response to hydrogen peroxide but not in response to salinity stress. Here we also isolated and cloned a gene encoding AmSOD1 which was classified into the group of plant CuZnSODs based on amino acid sequence analysis. AmSOD1 was heterologously expressed in the soluble fraction of E. coli strain Rosetta (DE3). The cells expressing His-AmSOD1 were more tolerant in response to hydrogen peroxide treatment but not salt stress, suggesting the involvement of AmSOD1 in hydrogen peroxide tolerance. The enzyme His-AmSOD1 exhibited a molecular mass of 38 kDa, but it could be monomer in reducing conditions indicating a double-strand protein with intra-molecular disulﬁde bridge. There are two copper and two zinc moles per mole of dimer form of His-AmSOD1 suggesting the binding of one copper and one zinc ions to each monomer. The Pure His-AmSOD1 was highly active in vitro and its activity was considerably enhanced when the growth medium of the cells producing AmSOD1 was supplemented with Cu 2+ . The high stability of the recombinant AmSOD1 after incubation in a broad range pH and high temperature is a distinctive feature for AmSOD1, which may open new insights for application of AmSOD1 as a protein drug in different medical purposes. Graphical abstract: Image 1 Highlights: The activity of SOD from Avicennia marina (AmSOD1) was increased in response to salt and hydrogen peroxide. SOD was accumulated in the leaves in response to hydrogen peroxide treatment but not salt stress. Am SOD1 from Avicennia marina which was heterologously expressed in the soluble fraction of E. coli. The presence of Cu 2+ is much more essential than Zn 2+ for folding, solubility and stability of AmSOD1. AmSOD1 is highly active in vitro in a board range pH and high temperature.